2011
DOI: 10.1093/hmg/ddr093
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of MECP2-null Rett Syndrome patient hiPS cells and isogenic controls through X-chromosome inactivation

Abstract: Rett syndrome (RTT) is a neurodevelopmental autism spectrum disorder that affects girls due primarily to mutations in the gene encoding methyl-CpG binding protein 2 (MECP2). The majority of RTT patients carry missense and nonsense mutations leading to a hypomorphic MECP2, while null mutations leading to the complete absence of a functional protein are rare. MECP2 is an X-linked gene subject to random X-chromosome inactivation resulting in mosaic expression of mutant MECP2. The lack of human brain tissue motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
239
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(261 citation statements)
references
References 61 publications
19
239
1
Order By: Relevance
“…Female fibroblast cell lines with no MeCP2 mutations (Detroit 551 or PGP9f) were also shown to become both monoallelic and biallelic iPSCs, suggesting that both the retention and reactivation of X chromosome status during reprogramming are not restricted to MeCP2 mutant cell lines. Recently, the Ellis group generated iPSCs from patients with RTT and similarly observed retention of the inactive somatic X chromosome in iPSCs (39), independently confirming our findings. Pluripotent ESCs derived from inner cell mass are considered to be in the "naïve" state and have two active X chromosomes, whereas pluripotent EpiESCs derived from epiblasts have undergone random XCI and considered to be in the "primed" state (28).…”
Section: Discussionsupporting
confidence: 87%
“…Female fibroblast cell lines with no MeCP2 mutations (Detroit 551 or PGP9f) were also shown to become both monoallelic and biallelic iPSCs, suggesting that both the retention and reactivation of X chromosome status during reprogramming are not restricted to MeCP2 mutant cell lines. Recently, the Ellis group generated iPSCs from patients with RTT and similarly observed retention of the inactive somatic X chromosome in iPSCs (39), independently confirming our findings. Pluripotent ESCs derived from inner cell mass are considered to be in the "naïve" state and have two active X chromosomes, whereas pluripotent EpiESCs derived from epiblasts have undergone random XCI and considered to be in the "primed" state (28).…”
Section: Discussionsupporting
confidence: 87%
“…Several mutations introduce premature stop codons throughout the gene and are predicted to result in a null allele. Cheung et al and Schanen et al have reported that phenotypic analysis of same genotype controls and neurons obtained from altered hiPS cells are the source to know the development of RTT and denotes the importance of MECP2 in human neurons (33,67). Consistent with RTT animal models and RTT post-mortem human brain tissue (68), both groups detected a decrease in cell soma size of RTT neurons compared with non-affected controls.…”
Section: Mecp2 In Rtt Patientsmentioning
confidence: 87%
“…The generation of hiPSCs from RTT patients represents an inexhaustible source for in vitro derived patient-specific neurons, assuming that RTT-hiPSCs can be expanded indefinitely with a normal karyotype and stable genome and the generation of patient-specific hiPSCs from RTT girls has been an area of intense research as several groups have reported the generation of such cells (14,(32)(33)(34)(35)84,85). RTT-hiPSCs generated by different groups have similar properties as they carry pathogenic mutations in MECP2 or CDKL5 and are pluripotent in vitro and in vivo.…”
Section: Hipsc In Rttmentioning
confidence: 99%
See 2 more Smart Citations